PROTEN TYROSINE PHOSPHATASE ACTIVITY IN RAT ASCITES HEPATOMA CELLS - M.Saadat; D.D. Farhud (Tehran University of Medical Sciences, 1998)
Protein tyrosine phosphatases (PTPases) regulate tyrosine phosphorylation of target proteins involved in several aspects of cellular functions. Enzyme activities of the PTPases in cytosolic and particulate fractions of rat ascites hepatoma cell lines were determined and compared with those of normal rat liver. Our present data revealed that although there was no neoplatic-specific alteration of the PTPase activity in examined hepatomas, the activity in particulate fractions of island type of hepatomas was remarkably decreased compared with either rat liver or free type hepatomas.